Ijarah Based Justice in On-Call Labor Wage Systems: A Qualitative Study of Local ISPs Business - Mohammad Saiful Rifai; Muchamat Amarodin; Yuni Maimuna; Fida Arumingtyas; Lina Marlina Susana (Musyarakah: Journal of Sharia Economic (MJSE), 2026)
Introduction/Main Objectives: The development of flexible work arrangements has encouraged the emergence of on-call labor systems in technology-based businesses, including local Internet Service Providers (ISPs). Background Problems: Although operationally efficient, this model raises concerns regarding contractual clarity, wage mechanisms, and Islamic justice. This study analyzes the wage system for on-call workers and its conformity with Islamic justice based on the ijarah contract. Novelty: This study extends the application of ijarah al-a'mal to flexible on-demand employment in technology-based micro-enterprises, demonstrating its relevance to contemporary informal labor relationships. Research Methods: A qualitative case study was conducted at Irvan WiFi in Blitar Regency, Indonesia. Data were collected through interviews, observations, and documentation involving three key informants consisting of one business owner and two purposively selected on-call workers. The data were analyzed using the Miles and Huberman interactive model through coding, categorization, theme development, and interpretation. Finding/Results: Wages are determined by the type of work, level of difficulty, and field conditions. The practice fulfills the essential elements of an ijarah contract despite being conducted orally and reflects the principles of 'adl, antaradhin, and maslahah through proportional wages, timely payments, and adaptive compensation. Conclusion: The on-call labor system represents a contemporary form of ijarah al-a'mal, showing that flexible employment relationships can remain consistent with Sharia principles when based on contractual clarity, justice, and mutual consent.